2023
DOI: 10.1002/esp.5683
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of suspended sediment dynamics along the shorelines of the Yellow River Delta detected from satellite data

Song Jin,
Sergio Fagherazzi,
Cedric G. Fichot
et al.

Abstract: Total suspended solids (TSS) can be a useful indicator of environmental change in nearshore coastal environments. Understanding the mechanisms of TSS variations in response to environmental drivers is of broad interest for ecology and geomorphology. The Yellow River Delta (YRD) in China is a fragile coastal region that has been affected by human activities and climate change. Here, we investigated TSS along the YRD shoreline over two decades with time‐series satellite data (2002–2020). We observed that TSS con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Previous research findings have consistently demonstrated that the dispersion patterns of suspended sediments are influenced by the dynamics of tidal currents [37,38]. Variations in suspended sediment concentrations are primarily induced by seasonal oscillations in sea surface elevation and wind-induced waves [39], with tidal level fluctuations regarded as short-term variations in sea surface elevation. Similarly, the distribution range of high SSC areas in this study may be related to tidal levels and wind speeds.…”
Section: Spatiotemporal Characteristics Of Sscmentioning
confidence: 91%
“…Previous research findings have consistently demonstrated that the dispersion patterns of suspended sediments are influenced by the dynamics of tidal currents [37,38]. Variations in suspended sediment concentrations are primarily induced by seasonal oscillations in sea surface elevation and wind-induced waves [39], with tidal level fluctuations regarded as short-term variations in sea surface elevation. Similarly, the distribution range of high SSC areas in this study may be related to tidal levels and wind speeds.…”
Section: Spatiotemporal Characteristics Of Sscmentioning
confidence: 91%
“…Here, we used estimates of SPM obtained by the ratio of red and green wavelengths in the Sentinel-3 A/B OLCI images. The SPM was derived using the following equation: log(SPM) = 4.289 × R rs (670)/R rs (555) + 0.0667 [56]. The SPM spatial pattern changes significantly in different seasons, and it is often specular to the particle size distribution (Figure 9a).…”
Section: Inorganic Sediments Dominate Spm Mapping Based On the Psd Sl...mentioning
confidence: 99%